Community and communication : the role of language in nation state building and European integration - Wright, Sue, 1947- (Multilingual matters (Series), 2000)
This book considers the issue of language in the European Union. With a community of communication, the European Union could develop democratic structures and legitimacy and give meaning to its policies of free movement. How to achieve that community of communication is the biggest challenge facing Europe today.